Heterogeneous nuclear RNPs as targets of autoantibodies in systemic rheumatic diseases - Op De Beéck, Katrijn; Maes, Liesbeth; Van den Bergh, Karolien; Derua, Rita; Waelkens, Etienne; Van Steen, Kristel; Vermeersch, Pieter; Westhovens, René; De Vlam, Kurt; Verschueren, Patrick; Hooijkaas, Herbert; Blockmans, Daniel; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2012)
Objective To investigate the abundance of autoantibodies to heterogeneous nuclear RNPs (hnRNPs) in systemic rheumatic diseases. Methods Recombinant human hnRNPs A1, B1, C1, E1, F, Gi, H1, I, K, and P2 were prepared. Antibodies to these antigens were determined by Western blotting and by enzyme‐linked immunosorbent assay (ELISA) (for hnRNPs B1, E1, F, and H1) in serum samples obtained from patients with chronic fatigue syndrome (control subjects) and from patients with various connective tissue diseases. Results Western blotting analysis in 106 control subjects and 298 patients with a connective tissue disease revealed that antibodies to all tested hnRNP antigens, except hnRNP Gi, were significantly more prevalent in patients with Sjögren's syndrome (SS) than in control subjects. The highest reactivity was observed for hnRNPs B1, E1, F, and H1 (reactivity in >45% of patients with SS and in 2.8% of control subjects). Reactivity with hnRNPs B1, E1, F, and H1 was also evaluated by ELISA in 89 control subjects and 228 patients with a connective tissue disease. Reactivity with at least 2 of the 4 tested antigens was observed in 1.1% of control subjects, 16% of patients with systemic lupus erythematosus (SLE), and 18% of patients with SS. Reactivity with at least 3 of the 4 antigens was observed in 0% of the control subjects, 3.2% of patients with SLE, and 15% of patients with SS. Conclusion Several hnRNPs are target antigens in SS. The combined presence of antibodies to several hnRNPs was strongly associated with connective tissue disease in general and with SS in particular.